The Role of Contractual Budgeting as a Tool for Planning and Control in Investment Budgeting: A Field Study in Iraqi Universities - SAIB , YAHYA HASHIM; LAJIMI , ADNENE (Journal of Ecohumanism, 2025)
This study aimed to identify the extent of the possibility of developing the state's general budget by stating the availability of the necessary components for the contractual budget method in the investment aspect of the budgets of Iraqi universities. And to determine the importance and advantages of the contractual budget method as a tool for planning and controlling the investment budget in Iraqi universities in the opinion of the sample members studied. The study methodology relied on the descriptive and analytical approach. The researcher used the questionnaire as the main tool for this study. The study community consisted of employees of Iraqi universities, as the number of Iraqi universities reached (36) universities. A sample consisting of workers in planning and budgeting, the financial manager, the investment accountant, and the internal control manager was selected to conduct the study on them. A sample of the study community, which numbered (194) people, was taken, and this type of community was tested for their specialization in the contractual budget. The questionnaire was distributed to the sample members, as (188) questionnaires were retrieved, and after examining them, (8) questionnaires were excluded for their unsuitability for analysis purposes. Thus, the number of questionnaires valid for analysis reached (180), using the statistical program (SPSS). The results showed that there are advanced legislative and regulatory capabilities to apply the contractual budgeting method when preparing and implementing the budgets of Iraqi universities. There are also planning and contractual capabilities applied when setting the estimated budgets for investment projects when preparing and implementing the budgets of Iraqi universities. There are advanced accounting and control capabilities to apply the contractual budgeting method when preparing and implementing the budgets of Iraqi universities. There are also advanced human and material capabilities to apply the contractual budgeting method when preparing and implementing the budgets of Iraqi universities. The study recommended the necessity of using the contractual budget in preparing and implementing the investment budget of Iraqi universities due to its advantages and the importance of qualifying and training workers in the field of planning, finance and budgets on modern methods in preparing the contractual budget.